Retinopathy in severe malaria in Ghanaian children - overlap between fundus changes in cerebral and non-cerebral malaria - Essuman, V.A.; Ntim-Amponsah, C.T.; Astrup, B.S.; Adjei, G.O.; Kurtzhals, J.A.L.; Ndanu, T.A.; Goka, B. (My University, 2010)
Abstract Background In malaria-endemic areas, reliably establishing parasitaemia for diagnosis of malaria can be difficult. A retinopathy with some features unique to severe malaria with a predictive value on prognosis, has been described. Detection of this retinopathy could be a useful diagnostic tool. This study was designed to determine the diagnostic usefulness of retinopathy on ophthalmoscopy in severe malaria syndromes: Cerebral malaria (CM) and non-cerebral severe malaria (non-CM), i.e. malaria with respiratory distress (RD) and malaria with severe anaemia (SA), in Ghanaian children. Secondly, to determine any association between retinopathy and the occurrence of convulsions in patients with CM. Methods and subjects A cross-sectional study of consecutive patients on admission with severe malaria who were assessed for retinal signs, at the Department of Child Health, Korle-Bu Teaching Hospital, Accra, from July to August 2002 was done. All children had dilated-fundus examination by direct and indirect ophthalmoscopy. Results Fifty-eight children aged between six months and nine years were recruited. Twenty six(45%) had CM, 22 with convulsion; 26(45%) had SA and six(10%) had RD. Any retinopathy was seen in: CM 19(73%), SA 14(54%), RD 3(50.0%), CM with convulsion 15(68%) and CM without convulsion 4(100%). Comparison between CM versus non-CM groups showed a significant risk relationship between retinal whitening and CM(OR = 11.0, CI = 2.2- 56.1, p = 0.001). There was no significant association with papilloedema(OR = 0.9, CI = 0.3 - 3.0, p = 0.9), macular whitening(OR = 1.6, CI = 0.5 - 4.8, p = 0.4), macular haemorrhage(OR = 0.28, CI = 0.03 - 2.7 p = 0.2), retinal haemorrhage(OR = 1.9, CI = 0.6 - 5.6, p = 0.3), vessel abnormality(OR = 1.9, CI = 0.6 - 6.1, p = 0.3) and cotton wool spots(OR not calculated, p = 0.08). Tortuous and engorged retinal veins, not previously described as a feature of CM, was the most common vascular abnormality(15/58 = 26%) and was detected even in the absence of papilloedema. Conclusion Retinal whitening, a sign suggestive of retinal ischaemia, was significantly more common in CM than in non-CM syndromes. However, the high prevalence of any retinopathy in the latter suggests that the brain and the retina may be suffering from ischaemia in both CM and non-CM.